Pengaruh Rekrutmen Dan Seleksi Terhadap Kinerja Karywan Pada Hotel Abadi Suite Kota Jambi - Azima, Khuluqon; AS, Sakinah; Mulyani, Ika (Universitas Batanghari Jambi, 2023)
This study aims to determine how the effect of recruitment and selection on employee performance at the Abadi Suite Hotel Jambi City simultaneously and partially and how much influence recruitment and selection have on employee performance at the Abadi Suite Hotel Jambi City.The object of this analysis is the Hotel Abadi Suite Jambi City. The sample used in this study were 38 employees at the Abadi Suite Hotel, Jambi City. The method used is descriptive analysis method with recruitment and selection independent variables while the dependent variable is employee performance. The analytical tool used in this research is multipleÂ linearÂ analysis, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, coefficient of determination and hypothesis testing (f test and t test).Based on the calculation results of SPSS version 22, the correlation between the recruitment variable (X1) is 0.468 and the selection variable (X2) is 0.472 on performance (Y), which means that there is a positive influence between recruitment and selection variables on employee performance and there is a strong relationship between the variables independent and the dependent variable is 71.6%.The conclusion of this study shows that recruitment and selection simultaneously have a significant effect on employee performance, partially recruitment and selection have a significant effect on employee performance.